First Record of Lactarius hatsudake (Russulaceae), A Wild Edible Mushroom from India - Chakraborty, Dyutiparna; Tudu, Debala; Das, Kanad; Ghosh, Aniket (Indian Forester, 2025)
Lactarius hatsudake, a reddish latex oozing member of Lactarius section Deliciosi was collected from forests of East Khasi Hills, Meghalaya. This species is well appreciated by the local tribal communities and sold in local markets during monsoon. Detailed macro- and micromorphological description, coupled with internal transcribed spacer region of ribosomal DNA (nrITS)-based phylogenetic estimation of this species is presented here. This species is reported for the first time from India.